The Effect of the Jigsaw Technique on the Knowledge and Skills of Nursing Students (Bangladesh Journal of Medical Science, 2022)
Background: The Jigsaw technique is a modern method that enables the creation of a positive learning environment.In this study, we aim to determine the impact of Jigsaw technique on students’ knowledge level regarding arterial blood pressure and their arterial blood pressure performance skill level.Material and Methods: A quasi-experimental design study was conducted 60 first year nursing students atSakarya University. Students in the control group received traditional learning method while the intervention group had Jigsaw technique activities. Data was collected through “Arterial Blood Pressure Knowledge Test” and “Arterial Blood Pressure Skill Performance Test”. Cronbach Alpha, Mann Whitney U Test, and Independent T-Test, were used for the data analysis.Results and Discussion: Arterial blood pressure knowledge level test score ranking average of the students in the intervention group were (42.38) significantly higher than those of control group (18.62) (p